Метод повышения достоверности распознавания речевых команд в сложных акустических условиях - Штепа, Александр Анатольевич; Колларов, Александр Юрьевич (НТУ "ХПИ", 2015)
В данной статье обсуждается применение методов обработки зашумленных сигналов в системах распознавания речевых команд и приводятся некоторые из результатов исследований в этой области. Основной целью исследования является повышения достоверности распознавания речевых команд в системах голосового управления техническими объектами в сложной акустической обстановке путем повышения соотношения сигнал/шум за счет применения пространственного разделения сигналов с помощью нескольких направленных микрофонов и цифровой обработки сигналов на основе адаптивной компенсации помех. Использование современных методов лингвистического распознавания речевых команд совместно с методом адаптивной компенсации для обработки зашумленного сигнала позволяет повысить достоверность распознавания речевых команд.

This article discusses the application of the methods of processing noisy signals in the systems of voice recognition and are some of the results of research in this area. The main purpose of the study is to improve the reliability of voice recognition systems voice control of technical objects in the noisy environment by increasing the ratio signal/noise due to the use of spatial separation of signals using multiple directional microphones and digital signal processing based on adaptive compensation of interference. The use of modern linguistic methods of speech recognition software in conjunction with the adaptive compensation method for processing a noisy signal can improve the accuracy of speech recognition software. As a criterion for defining the main channel was proposed to use the measure of closeness between the received signal and the reference obtained by the command recognition method based on nonlinear time alignment. The research results can be applied to voice recognition in voice control of technological equipment and means of transport.
Method of improving the voice recognition reliability in difficult acoustic conditions
Keywords: голосовое управление; адаптивная компенсация; аддитивный шум; обработка зашумленных сигналов; voice control; speech recognition; adaptive compensation; additive noise